The Cold Chain Question: Effects of Fresh, Frozen, and Thawed Beef Trim on Ground Beef Color and Consumer Perception - Samuel F. Stickley (Kansas Agricultural Experiment Station Research Reports, 2026)
Objective: The objective of this study was to evaluate the effect of varying cold chain management strategies on beef trim and the resulting effects on quality characteristics of ground beef patties. Study Description: Beef trim of varying lean percentages (50%, 80%, and 90%) and cold chain strategies (fresh, thawed, and frozen) were ground and combined to create 10 unique treatments of 80% lean ground beef. These treatments were formed into 1/3 lb patties and subjected to 0 + 5 days of simulated retail display. On each day of display, objective color measurements were taken. On day 0 + 3 of retail display, consumer evaluations were conducted as well as Thiobarbituric Acid Reactive Substances (TBARS) assays to measure lipid oxidation. The Bottom Line: Results from this study suggest grinding trim from a frozen state has a detrimental effect on ground beef color, oxidation, and the resulting consumer perception.
Keywords: beef trim; ground beef; imported beef